Media sensory curation and family media conflict: replication and validation of short-form measures. Issue 4 (4th July 2021) - Harrison, Kristen; Couture Bue, Amelia
ABSTRACT: Media sensory curation theory conceptualizes sensory regulation within the built environment as a gratification of electronic media use and predictor of parent-child conflict over children's media use. This paper replicates an initial survey of caregivers of children ages 3 to 14 with an independent replication survey of N = 754. As in the original study, media sensory curation was higher among children with sensory diagnoses (e.g., autism, ADHD) than without and was a moderate to strong predictor of problematic child media use and adult-child media conflict for all children. The 48-item Adult and Child Media Sensory Curation Inventories (MediaSCIs) were subject to scale-reduction analyses using the pooled samples ( N = 1543) to create short-form scales. The resulting Adult MediaSCI-SF and Child MediaSCI-SF (12 items each) showed good reliability. The Child MediaSCI-SF predicted problematic child media use and media conflict as robustly as the 48-item Child MediaSCI. The MediaSCI-SF scales are parsimonious options for measuring media sensory curation.